NGIKIS Traditional Ceremony in Ciamis Regency (Study of Meaning, Value of Local Wisdom and Its Relevance in Historical Learning at MAN 2 Ciamis) - Hidayatuloh, Sarip; Musaddad, Ahmad Arif; Ediyono, Suryo (Budapest International Research and Critics University, 2021)
Ngikis traditional ceremony is one form of local wisdom in Ciamis Regency which until now is still done, considering the people of Karangkamulyan believe there is a charge of meaning and values in it. The meaning and values of local wisdom, have relevance to the learning of History in MAN 2 Ciamis. The purpose of this study is to describe and explain: (1) meaning; (2) local values of wisdom; and (3) relevance of the values of local wisdom of Ngikis traditional ceremonies Ngikis traditional ceremony with history learning at MAN 2 Ciamis. The method used in this study is a qualitative method with an ethnographic approach. The data collection technique performed is 1) Observation; 2) Interview; and 3) Documentation. The results showed: 1) the meaning of the Ngikistraditionalceremony, namely: as a form of respect for the ancestors of public Karangkamulyan, and also as a means to the fence and cleanse themselves from all despicable traits, then as an expression of gratitude to God YME for the sustenance that has been given; 2) the values of local wisdom, including values: religious, social, history, culture, ethics, and compassion, compassion, Admission; 3) relevance of Ngikis traditional ceremonies to Historical learning, which can create learning based on local culture and educational value in MAN 2 Ciamis